Crimean-Congo Hemorrhagic Fever Virus among Goats, Southern Bhutan - Rinchen, Sangay; Kaku, Yoshihiro; Park, Eunsil; Sharma, Puspa Maya; Tshering, Dawa; Tenzin, Tenzinla; Matsuu, Aya; Okutani, Akiko; Maeda, Ken; Morikawa, Shigeru (Emerging infectious diseases, 2025)
We conducted serosurveillance for Crimean-Congo hemorrhagic fever virus (CCHFV) among goats in southern Bhutan. Testing serum samples from 472 goats for CCHFV-specific IgG using an indirect fluorescent antibody test and ELISA, we found CCHFV antibody-positive goats along the analyzed border region with India, indicating widespread distribution of CCHFV in this area.